Sustainability Reporting as a Moderator in the Relationship Between Financial Performance and Stock Prices: An Empirical Analysis - Martin, Rio; Murdiansyah, Isnan (E-Jurnal Akuntansi, 2025)
Stock price fluctuations are inherently unpredictable and can occur at any time. In response to this volatility, the present study examines the influence of Net Profit Margin, Return on Assets, and Firm Size on Stock Prices, with Sustainability Reporting serving as a moderating variable. A quantitative research design is employed, focusing on financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using purposive sampling, a total of 16 companies were selected, resulting in 64 observations. The data analysis is conducted through moderation regression analysis, utilizing the E-Views version 12 software. The empirical results reveal that Net Profit Margin has a positive and significant effect on stock prices, whereas Return on Assets exhibits a negative influence. Firm Size does not demonstrate a statistically significant impact on stock prices. Moreover, the findings indicate that Sustainability Reporting strengthens the relationship between Net Profit Margin and stock prices. These results suggest that the disclosure of sustainability information can influence investment decision-making, offering insights that extend beyond traditional financial performance metrics. Keywords: Stock Price; Net Profit Margin; Return on Asset; Sustainability Report; Company Size